More Than Being Housewives: Images and Roles of Women in Folk Music and ItsPerformance in Northern Nigeria - Haruna, Zainab (Ethnologies, 2000)
Many women in northern Nigeria have been treated as second class citizens, and some are still treated that way. They are expected to focus more on their traditional role as housewives and mothers than on being political leaders, religious leaders and civil servants. Yet, both Muslim and Christian women in northern Nigeria are increasingly employing effective strategies that could help them to resist those restrictions and prove to their male counterparts that they can contribute to the educational, social and economic development of Nigeria if given the opportunity. An effective medium through which women of northern Nigeria sell their capabilities and potentialities is their music and musical performances. Perhaps it is safe to say that women’s involvement in politics and public services has been strengthened partially through their “rebellious” musical actions. This article describes and examines the images and roles of women as depicted in women’s folk music and folk music performances in northern Nigeria.